Local current leakage at threading dislocations in GaN bulk single crystals grown by a modified Na-flux method. (25th April 2019) - Hamachi, Takeaki; Tohei, Tetsuya; Imanishi, Masayuki; Mori, Yusuke; Sakai, Akira
Abstract: We have investigated the local electrical and structural properties of threading dislocations (TDs) in Na-flux-grown GaN bulk single crystals that consist entirely of c -plane growth sectors. Conductive atomic force microscopy analysis of Schottky-like contacts locally fabricated on dislocation-related etch pits showed a variety of leakage current under reverse bias conditions. Microstructural analysis around TDs revealed a correlation between the current leakage and the structure of the TDs and their surroundings. Microscale faceted growth sectors with a higher oxygen impurity concentration locally formed in the vicinity of TDs had a larger influence on the current leakage than the structure of TDs.